The biotechnology of higher fungi - current state and perspectives - Turło, Jadwiga (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2014)
This review article concisely describes methodology of biotechnological processes with the use of cultures of higher fungi, their application in bioremediation and to obtain biologically active preparations. Advantages and disadvantages of biotechnological methods used to cultivate mushrooms are analyzed. This paper contains overview of higher fungi species most commonly used in biotechnological processes, of cultivation methods applied to produce fungal biomass, of enzymes and bioactive metabolites and of the strategies for submerged cultivation of the mycelial cultures. The problems of optimization of strains and biotechnological processes are briefly discussed.